EFFECT OF DAHLIA TUBER INULIN EXTRACT ON THE THICKNESS OF THE THORACIC AORTIC TUNICA INTIMA-MEDIA IN TYPE 2 DIABETIC RATS MODEL - Natswa Deanra, Cantika; Ismawati, Ismawati; Saryono, Saryono; Juananda, Desby; Anggraini, Suci; Agung S, Timotius; Dayu Putri, Veni; Yanti, Sri; Dyna, Fitri (Universitas Muhammadiyah Surakarta, 2026)
Inulin is a natural polysaccharide that improves glucose metabolism and reduces cholesterol levels through the formation of short-chain fatty acids, which may contribute to preventing atherosclerosis in type 2 diabetes mellitus (T2DM). Therefore, this study aimed to evaluate the effect of dahlia tuber inulin extract on the thickness of the thoracic aortic tunica intima-media (TIM) in T2DM-induced rats. A total of 20 male Wistar rats were divided into five groups: control, T2DM, T2DM + 0.5 mg/gBW/day inulin extract, T2DM + 1.0 mg/gBW/day inulin extract, and T2DM + 1.5 mg/gBW/day inulin extract. T2DM induction was performed using 60 mg/kgBW streptozotocin and 120 mg/kgBW nicotinamide. Measurement of TIM thickness was conducted using a Leica light microscope with hematoxylin-eosin staining. The results showed no statistically significant differences among the groups (p = 0.051), although a decreasing trend in TIM thickness was observed at the 1.5 mg/gBW/day dose. In this context, dahlia tuber inulin extract demonstrated a tendency to reduce TIM thickness in T2DM-induced rats.